The potential of international cooperative initiatives to address key challenges of protected areas. Issue 136 (October 2022) - Negacz, Katarzyna; Petersson, Matilda; Widerberg, Oscar; Kok, Marcel; Pattberg, Philipp
Abstract: Protected areas are frequently used as an important governance approach for biodiversity conservation. Even though the total area of protected areas has increased over time, the coverage, quality of management and effectiveness of these areas are still suboptimal. A large body of literature identifies four main challenges that limit the effectiveness of protected areas: lack of stakeholder participation, insufficient organisational capacity to enforce rules, poor integration across social and ecological goals, and underdeveloped accountability mechanisms for assessing management procedures. To address these challenges, scholars and policymakers increasingly debate how to foster an integrated, inclusive, and transparent "whole of society" approach to conservation. We contribute to this debate by examining the role of international cooperative initiatives (ICIs), involving non-state and subnational actors operating across national borders to steer society towards a common goal. We identify 20 ICIs that work on protected areas and analyse their potential to address the four main challenges identified in protected areas, by examining their actor constellation, governance functions, goal alignment, and monitoring and reporting mechanisms. We find that ICIs working on protected areas have the potential to directly address challenges in protected areas related to lack of capacity and accountability mechanisms, and indirectly address challenges related to lack of participation and integration across goals. We discuss these findings in relation to scholarly debates in the global environmental governance and protected areas literature respectively, as well as, to policy debates over the post-2020 Global Biodiversity Framework within the Convention on Biological Diversity (CBD). Highlights: We identify 20 international cooperative initiatives (ICIs) working on protected areas. These ICIs can directly and indirectly address key challenges in protected areas. They are mostly civil society and public-led and engaged in information sharing. Their goals are well-aligned with global objectives on conservation and sustainable use.